“THE SCORPION FROM THE ALTAR” NOVEL AND THE NATIONAL SPIRIT OF UZBEK LITERATURE - Rayimqulov , Diyorbek (INTERNATIONAL MULTIDISCIPLINARY SCIENCE CONFERENCE, 2026)
“Mehrobdan Chayon” was written during a period of sharp transformation in Turkestan at the beginning of a new era. Through the novel, Qodiriy reveals the roots of such social vices as moral decline, careerism, ignorance, backwardness, and injustice. The work places the “scorpion” — symbolizing betrayal, hypocrisy, and oppression — alongside the symbols of “love” and “justice,” exposing the hidden cruelty concealed beneath seemingly noble values.